Drug Utilization and Drug Pricing in the Private Primary Healthcare System in Malaysia: An Employer Price Control Mechanism - Zin, Che Suraya; Taufek, Nor Hidayah; Bux, Siti Halimah (Frontiers in Public Health, 2020)
Uncontrolled drug pricing in the private healthcare system in Malaysia leads to high drug prices; however, its impact on employee drug utilization and employer reimbursement coverage is unclear. This study examined patterns of drug pricing and drug utilization among employees covered by employer medical insurance. A drug price control mechanism was also devised for the employer to ensure fair benefits to all parties without compromising the quality of patient care. This retrospective study was conducted among International Islamic University Malaysia (IIUM) community members who sought outpatient treatment at the IIUM panel of health clinics serviced by general practitioners from January 2016 to September 2019. Prescription data (drug type, dose, quantity, duration, price, and manufacturer), patient characteristics (age, sex, and diagnosis) and total charges were extracted from the claims database of PMCare, the insurance company managing IIUM medical claims. Patterns of commonly prescribed drugs, drug pricing, profit margins, and total charges per clinic visit were evaluated. Descriptive statistics were used, and all analyses were performed using Stata v15.1. There were a total of 161,146 prescriptions for 10,150 patients in the IIUM community during the study period (48.85% women, mean ± standard deviation; age: 26.33 ± 17.63 years). The most commonly prescribed drug was paracetamol (25.3%), followed by chlorpheniramine (9.46%), cetirizine (7.3%), diphenhydramine (6.13%), loratadine (4.57%), and diclofenac (4.36%). Generic paracetamol (500 mg), which serves as a prime example for details on drug pricing, is commonly charged between Ringgit Malaysia (RM) 5 and 10 for 10 tablets with a profit between 2,400 and 4,900% according to the average cost price of RM 0.20 per 10 tablets. Most patients were charged within the approved coverage limit of RM 45 per clinic visit, with only 2.41% of patients being charged with costs that exceeded this limit. Uncontrolled drug pricing in the private healthcare system in Malaysia indicates that drug prices differ greatly across private healthcare providers most of the prices were charged with high profit margins. Employers may consider a multilayer capping system to prevent inappropriate drug pricing, which will inevitably benefit patients clinically and economically and provide greater patient access to better drug treatment.